A Review on the Recent Development of Planar Snake Robot Control and Guidance - Ningwei Li; Fei Wang; Shanjun Ren; Xin Cheng; Gang Wang; Peng Li (Mathematics)
Snake robots, inspired by the biology of snakes, are bionic robots with multiple degrees of freedom and strong robustness. These robots represent a current area of significant research interest within the field of robotics. Snake robots have a wide range of applications in many fields, advancing the integration of bionics, robotics, and cybernetics, while playing a crucial role in performing survey and rescue missions. This survey presents the latest technological advancements in modeling, motion control, and guidance laws for planar snake robots, and provides a unified perspective based on the existing results. To achieve target-tracking control of robots in complex environments, we present a feasible approach that integrates guided vector field technology and transforms the target-tracking and obstacle avoidance problem into a reference angle tracking issue. Finally, this paper analyzes and summarizes the development process and key technologies of snake robot control and provides an outlook on future development trends.